Bibliometric overview of research trends on heavy metal health risks and impacts in 1989–2018. (10th December 2020) - Han, Ruru; Zhou, Beihai; Huang, Yuanyi; Lu, Xiaohui; Li, Shuo; Li, Nan
Abstract: Health risks caused by heavy metal pollution are one of the most concerning issues globally due to heavy metal toxicity, carcinogenicity, bioaccumulation, and complex mechanisms with multiple sources and pathways. Much effort has been devoted to researching heavy metal emissions, pollution, health risk assessments, and mitigation strategies in past decades. In this study, a bibliometric analysis of heavy metal health risks and impacts was performed to obtain an overview of the health risk levels, sources and control strategies of heavy metals in various regions worldwide in 1989–2018. The results showed there was a significant increase in the concern over heavy metal risks and impacts in the past ten years, especially in China and other developing countries. China surpassed the USA and became the most productive country in 2010; furthermore, China has contributed to nearly one-half of the total growth caused by increasing concerns about severe heavy metal pollution issues. The most concerning issues can be categorized into five hotspots: 1) soil-to-plant-to-dietary intake is the primary exposure pathway for public health, with the main pollutants being Cd, As and Pb, especially in China and other developing countries; 2) fish/shellfish consumption is the main exposure pathway for Hg intake, which is especially affected by methylmercury bioaccumulation in aquatic organisms; 3) the reduction of health risks caused by arsenic in drinking water, especially in Bangladesh and Pakistan due to natural geochemical sources, is important; 4) heavy metals in road dust and room dust combined with atmospheric emissions and air quality represent a research hotspot in the last decade; and 5) comprehensive assessment methods and related policies are popular research topics. Graphical abstract: Image 1